Rapid at‐line early cell death quantification using capacitance spectroscopy. Issue 3 (11th January 2022) - Wu, Suyang; Ketcham, Stephanie A.; Corredor, Claudia C.; Both, Douglas; Drennen, James K.; Anderson, Carl A.
Abstract: Cell death is one of the failure modes of mammalian cell culture. Apoptosis is a regulated cell death process mainly observed in cell culture. Timely detection of apoptosis onset allows opportunities for preventive controls that ensure high productivity and consistent product quality. Capacitance spectroscopy captures the apoptosis‐related cellular properties changes and thus quantifies the percentage of dying cells. This study demonstrated a quantification model that measures the percentage of apoptotic cells using a capacitance spectrometer in an at‐line setup. When predicting the independent test set collected from bench‐scale bioreactors, the root‐mean‐squared error of prediction was 8.8% (equivalent to 9.9% of the prediction range). The predicted culture evolution trajectory aligned with measured values from the flow cytometer. Furthermore, this method alarms cell death onset earlier than the traditional viability test, that is, the trypan blue exclusion test. Compared to flow cytometry (the traditional early cell death detection method), this method is rapid, simple, and less labor‐intensive. In addition, this at‐line setup can be easily transferred between scales (e.g., lab‐scale for development to manufacturing scale), which benefits process transfers between facilities, scale‐up, and other process transitions. Abstract : Capacitance spectra of samples collected from the lab‐scale bioreactor quantitatively predicted the dying cell percentage with the help of a partial least square regression model. The model described a culture trajectory that aligned with the flow cytometer method (stained with To‐Pro‐3). This model also captured the cell death onset earlier than the traditional viability test.